Narciso y Dioniso en W. Pater y O. Wilde - Martínez Victorio, Luis (Amaltea. Revista de Mitocrítica, 2008)
The Greek myths had a very significant presence in Victorian culture. The dominant tendency was to integrate them as a part of a culture characterised by a transcendent view of history, which was based on a synthesis of the metanarratives of enlightened modernity and protestant/puritanical religion. Myths were represented in accordance with the ethos emerging from such a context. At the Fin de Siècle, this representation was challenged by new ideological stances, partly aroused by an economic crisis which shook the foundations of the Victorian paradigm. The mythical figures of Dionysus and Narcissus played a very important role in the development of the Fin de Siècle culture. In other words, the reinterpretation of these myths, carried out during this period, underlies the challenging and postmodern patterns of the art and literature of the last decades of the 19th century. In the following pages the author discusses this process, and analyses a short-story by Walter Pater and two tales by Oscar Wilde in order to illustrate it.
Keywords: Greek myths